Awareness and Energy Conservation Behaviors: A Case Study of Institutional Buildings in Hail, Saudi Arabia - Mesloub, Abdelhakim; Alghaseb, Mohammed A.; Al-Sabhan, Nawwaf (International Journal of Architectural Engineering Technology, 2025)
The growing challenges of carbon emissions and global warming necessitate global efforts to improve energy efficiency and reduce energy consumption. The Kingdom of Saudi Arabia (KSA) faces significant challenges in ensuring a sustainable electricity supply in buildings, including high energy demand driven by extreme climate conditions, heavy reliance on fossil fuels, and inefficiencies in energy distribution and consumption patterns. This study explores the relationship between employee awareness, energy conservation behaviors, and electricity consumption in three architecturally identical institutional buildings in Hail province, which exhibit significant variations in energy use. Using a mixed method of qualitative and quantitative approaches, structured questionnaires were distributed to 27 employees, with 21 responses analyzed through SPSS using a five-point Likert scale. Results reveal that behavior, rather than awareness, is the primary driver of energy consumption, as Building 3 exhibited the highest energy-saving behaviors despite moderate awareness levels. Workplace norms, peer influence, and reinforcement mechanisms significantly impact energy-saving actions, while awareness alone proves insufficient in fostering consistent behavioral engagement.